2012
DOI: 10.1002/pssa.201200023
|View full text |Cite
|
Sign up to set email alerts
|

2 MeV e‐irradiation UHVEM study on the impact of O and Ge doping on {113}‐defect formation in Si

Abstract: First results are presented of a study on the impact of O and Ge doping on {113}‐defect formation in Si using in situ 2 MeV e‐irradiation in a high voltage electron microscope. Comparison with undoped Si, reveals a suppression of {113}‐defect formation due to O and Ge. The observations are discussed in the frame of a theoretical model assuming quasi‐chemical reactions to describe the intrinsic point defect behaviour during irradiation as a function of irradiation temperature and specimen thickness. It is shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 26 publications
(27 reference statements)
1
16
0
Order By: Relevance
“…Although the experimental observations in the present work and also in our previous studies on {113}-defect formation in Si [15,19] are in excellent agreement with the experimental observations in the pioneering work of the Aseev group [8,9,12], the interpretation and modeling is quite different due to the progress which has been made in the mean time in understanding the Si intrinsic point defect properties. At the end of the 1980's, one assumed that during irradiation the diffusivity of the interstitial was larger than that of the vacancy and for that reason one needed to assume an important contribution of athermal interstitial diffusion to explain the experimental observations on {113}-defect formation.…”
Section: Vacancy and Interstitial Diffusivitysupporting
confidence: 81%
See 2 more Smart Citations
“…Although the experimental observations in the present work and also in our previous studies on {113}-defect formation in Si [15,19] are in excellent agreement with the experimental observations in the pioneering work of the Aseev group [8,9,12], the interpretation and modeling is quite different due to the progress which has been made in the mean time in understanding the Si intrinsic point defect properties. At the end of the 1980's, one assumed that during irradiation the diffusivity of the interstitial was larger than that of the vacancy and for that reason one needed to assume an important contribution of athermal interstitial diffusion to explain the experimental observations on {113}-defect formation.…”
Section: Vacancy and Interstitial Diffusivitysupporting
confidence: 81%
“…for z = −l and z = l), and also that dC I,V /dz = 0 for z = 0, the solution of (1) is given by [15,20] …”
Section: Irradiation At 375mentioning
confidence: 98%
See 1 more Smart Citation
“…In both structures, extensive {113}-defect formation is observed in the n + substrate after 12 min irradiation. solution of (2) is given by [13,18] …”
Section: Samples For In Situmentioning
confidence: 99%
“…to transient enhanced diffusion of dopants. It was shown that heavy doping with B or P, the presence of interfaces and local stress fields as well as the irradiation temperature and the specimen thickness, have an influence on the {113}-defect formation kinetics and stability in thin Si foils [7][8][9][10][11][12][13]. In the mean time, the growth behavior of {113}-defects is also well understood [14].…”
Section: Introductionmentioning
confidence: 99%